Allosteric gating mechanism underlies the flexible gating of KCNQ1 potassium channels - Osteen, Jeremiah D. (National Academy of Sciences, 2012)
KCNQ1 (Kv7.1) is a unique member of the superfamily of voltage-gated K(+) channels in that it displays a remarkable range of gating behaviors tuned by coassembly with different β subunits of the KCNE family of proteins. To better understand the basis for the biophysical diversity of KCNQ1 channels, we here investigate the basis of KCNQ1 gating in the absence of β subunits using voltage-clamp fluorometry (VCF). In our previous study, we found the kinetics and voltage dependence of voltage-sensor movements are very similar to those of the channel gate, as if multiple voltage-sensor movements are not required to precede gate opening. Here, we have tested two different hypotheses to explain KCNQ1 gating: (i) KCNQ1 voltage sensors undergo a single concerted movement that leads to channel opening, or (ii) individual voltage-sensor movements lead to channel opening before all voltage sensors have moved. Here, we find that KCNQ1 voltage sensors move relatively independently, but that the channel can conduct before all voltage sensors have activated. We explore a KCNQ1 point mutation that causes some channels to transition to the open state even in the absence of voltage-sensor movement. To interpret these results, we adopt an allosteric gating scheme wherein KCNQ1 is able to transition to the open state after zero to four voltage-sensor movements. This model allows for widely varying gating behavior, depending on the relative strength of the opening transition, and suggests how KCNQ1 could be controlled by coassembly with different KCNE family members.